THE IMPLEMENTATION OF TWO STAY TWO STRAY TECHNIQUE TO IMPROVE THE STUDENTS’ COMPETENCE OF SMP NEGERI 9 BANDA ACEH IN MASTERING READING COMPREHENSION - Ghina Sabrina; Budi Rizka; Sariakin Sariakin (JETLi: Journal of English Teaching and Linguistics, 2020)
The aims of the study are to find out how the students’ ability of SMP Negeri 9 Banda Aceh in mastering reading comprehension is after they are taught by using two stay two stray technique and to find out if there is a significant difference between the students’ ability of SMP Negeri 9 Banda Aceh who are taught by using two stay two stray technique and those who are taught without using two stay two stray technique in mastering reading comprehension. The design that is used in this research is an experiment research. The experiment research is used to find out the effect of treatment in teaching reading skill by using two stay two stray technique. The total population of this research is 122 students who are composed of four classes; VIII1, VIII2, and VIII3, and VIII4. While the sample of this study is taken from two of the four classes. In this research, the students of class VIII2 are as experimental group and the students of VIII1 are as control group. Every class consists of 20 students thus the total sample is 20 students. The data are collected through test. The data gotten are analyzed by using t-test. The result of t-test calculation shows that t-test (2.31) than critical value of t-test for the degree freedom of 38 is 2.02 at the level of significance 0.05 or the value t significance (0.027) is smaller than 0.05 (p<0.05).  It means that Ho is rejected and Ha is accepted.